Determinants of children ever born among ever-married women in Bangladesh: evidence from the Demographic and Health Survey 2017–2018 - Atikur Rahman; Zakir Hossain; Mohammad Lutfor Rahman; Enamul Kabir (BMJ Open, 2022)
Objective To investigate the prevalence of the number of children ever born (CEB) and its associated determinants among women aged 15–49 years in Bangladesh.Study design and setting We used clustered data extracted from the last two Bangladesh Demographic and Health Surveys (BDHS 2014 and BDHS 2017–2018). A two-stage stratified sampling was used in both surveys. Mixed logistic regression modelling approach for binary responses was adapted to accommodate clustering effects via the generalised linear mixed model framework.Participants The study is based on 15 924 ever-married women in BDHS 2017–2018 (14 119 in BDHS 2014) of Bangladesh.Results As per the latest BDHS 2017–2018, 42.1% of reproductive women had three or more children. Age at first marriage (p<0.001, OR 0.74, 95% CI 0.666 to 0.825), age at first birth (p<0.001, OR0.54, 95% CI 0.480 to 0.607), place of residence (p<0.001, OR 0.79, 95% CI 0.712 to 0.872), exposure of media (p<0.001, OR 0.71, 95% CI 0.647 to 0.768), religion (p<0.001, OR 1.47, 95% CI 1.277 to 1.690), husband’s desire more child (p<0.001, OR 1.60, 95% CI 1.428 to 1.784), women empowerment (p<0.001, OR 1.19, 95% CI 1.075 to 1.3) and wealth index (p<0.001, OR1.61, 95% CI 0.435 to 1.796) were found to be statistically significant determinants of the number of CEB among ever-married women. The number of CEB among women was negatively associated with their own educational status (p<0.001) and husbands level of education (p<0.001).Conclusion The CEB appears to be higher among women who were married before 18 years, Muslim, illiterate, living in rural areas, had first birth before 20 years, non-exposure of media and husband’s desire for more children.